2020
DOI: 10.5334/bc.15
|View full text |Cite
|
Sign up to set email alerts
|

Thermally resilient communities: creating a socio-technical collaborative response to extreme temperatures

Abstract: Extreme temperatures claim more lives than any other weather-related event, posing escalating socio-technical and governance challenges that few urban communities have addressed in a systematic, coordinated and comprehensive way. Scholars have only recently begun to investigate the granular scales at which distributions of thermal risk are produced, people's individual subjective thermal experiences and environmental justice dimensions of the hazard. Advances in research pave the way for concomitant improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 39 publications
(28 reference statements)
0
13
0
Order By: Relevance
“…However, these programs were developed without explicitly incorporating climate change (e.g., considering the implications of projections of future risks), meaning they may be ill-equipped to manage the health impacts associated with increases in the frequency and intensity of extreme events. Furthermore, some climaterelated hazards, like extreme heat, fall outside of the official or perceived domains of responsibility for professional disaster management agencies or are approached through a distributed governance model with no designated lead entity (68). The key policy levers for health-sector decision makers are climate change adaptation, GHG mitigation, and disaster risk management.…”
Section: Increasing the Resilience Of Health Systemsmentioning
confidence: 99%
“…However, these programs were developed without explicitly incorporating climate change (e.g., considering the implications of projections of future risks), meaning they may be ill-equipped to manage the health impacts associated with increases in the frequency and intensity of extreme events. Furthermore, some climaterelated hazards, like extreme heat, fall outside of the official or perceived domains of responsibility for professional disaster management agencies or are approached through a distributed governance model with no designated lead entity (68). The key policy levers for health-sector decision makers are climate change adaptation, GHG mitigation, and disaster risk management.…”
Section: Increasing the Resilience Of Health Systemsmentioning
confidence: 99%
“…As mentioned, extreme heat control measures have received less attention in comparison with other hazards such as floods. [ 75 ] A study listing 3,500 online resources for climate adaptation found that only 4% focused on heat, while 21% focused on sea level rise and 14% on flooding. In addition, while thermal planning research is growing rapidly, 60% of papers published between 2013 and 2018 focused on modeling, and only <7% focused on planning processes and executive actions.…”
Section: Discussionmentioning
confidence: 99%
“…The role of technology, specifically concerning ubiquitous sensing and Internet‐of‐Things connectivity will need to be carefully balanced (Section 2.3). Governance actors can benefit from access to increasingly precise data about urban climates and urban systems that influence and are influenced by the urban climate (Hamstead et al., 2020; Hondula et al., 2015; Y. Yin et al., 2020), but widespread sensing raises potential social and legal challenges concerning privacy and security, institutionalization of bias, and more. Given the complexities and interrelationships of the challenges associated with urban overheating, adaptive governance may be the most promising model for localities to adopt as they move forward.…”
Section: Multidisciplinary Solutions To Address Urban Overheatingmentioning
confidence: 99%